جلال آل أحمد حياته ونتاجه الأدبي في إيران 1923 – 1969 - العكيلي, م. د. حيدر علي خلف جودة (Thi Qar Arts Journal, 2021)
Jalal Al-e Ahmad was born to a clerical religious family in Tehran in 1923. A teacher all his life, he joined the Communist "Tudeh Party" in 1943 and quickly rose through its ranks, becoming a member of the party committee for Tehran, before breaking with the "Tudeh" in 1947 in protest over Soviet influence. Al-e Ahmad was an influential and prolific writer and social critic, whose body of work includes short stories, notably the collection An Exchange of Visits; novels including By the Pen, The School Principal, and A Stone on a Grave; travelogues including A Straw in Mecca, A Journey to Russia, and A Journey to America; anthropological studies; essays; reviews; and translations. His best known work is Gharbzadegi (Occidentosis), which has also been translated to English, a cultural critique of Westernization in Iran.Jalal Al Ahmed was considered one of the theorists of the Iranian revolution and on the words of its top leaders, especially Ayatollah Ali Khamenei, who praised his ideas and positions opposing injustice and persecution, and his books are still very popular inside and outside Iran. He died in 1969, and suspicions were raised that the SAVAK was involved in his death.